Waste graphite regeneration method, regenerated graphite negative electrode material and secondary battery

By employing a process of calcination, shaping, graphitization, and carbon coating, the problem of recycling high-impurity waste graphite has been solved, enabling the production of efficient, economical, and environmentally friendly recycled graphite anode materials, thereby improving battery performance and resource recycling efficiency.

CN120987314APending Publication Date: 2025-11-21GUANGDONG BRUNP RECYCLING TECH CO LTD +3

Patent Information

Application Number
CN202511146944.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively recycle waste graphite with high impurity content, leading to resource waste and environmental pollution. Furthermore, existing processes cannot simultaneously achieve efficient impurity removal, economic feasibility, and environmental friendliness.

Method used

The process involves calcination, shaping, graphitization, impurity removal, and carbon coating. This includes oxidative calcination to remove organic matter, shaping and grading to control particle size, graphitization to improve crystallinity, acid washing and water washing to remove metallic impurities, and carbon coating to form a core-shell structured regenerated graphite anode material.

Benefits of technology

It has achieved the regeneration of high-purity, high-capacity, long cycle life and fast-charging performance high-quality battery-grade graphite anode materials, solved the problem of resource recycling of waste graphite, and met the needs of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987314A_ABST
    Figure CN120987314A_ABST
Patent Text Reader

Abstract

The invention discloses a waste graphite regeneration method, a regenerated graphite negative electrode material and a secondary battery, and the waste graphite regeneration method comprises the following steps: roasting: carrying out oxidizing roasting on waste graphite slag to obtain roasted graphite; shaping: shaping and grading the roasted graphite to obtain shaped graphite; graphitization: graphitizing the shaped graphite to obtain coarse graphite; and impurity removal: performing impurity removal on the coarse graphite to obtain impurity-removed graphite. According to the method for regenerating the waste graphite, waste is turned into wealth, and the problems of environmental pollution and resource waste when the waste graphite slag is treated as solid waste are solved; the used equipment is industrial equipment mature in the market, the technology is mature, safety and reliability are achieved, the investment cost is low, and the large-scale production requirement can be met. Importantly, the high-quality battery-grade graphite negative electrode material with high purity, high capacity, long circulation and good fast charging performance can be obtained, and finally the cyclic utilization of turning waste into wealth is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lithium ion battery negative electrode materials, in particular to a method for regenerating spent graphite, a regenerated graphite negative electrode material and a secondary battery. BACKGROUND

[0002] Graphite is considered as the ideal negative electrode material for lithium ion batteries due to its excellent electrical and thermal conductivity, stable crystal structure and good electrochemical properties. It currently accounts for more than 95% of the global negative electrode material market. According to industry statistics, the global negative electrode material shipment volume reached 1.785 million tons in 2023, a significant increase from 163,000 tons in 2017. With the arrival of the large-scale retirement period of lithium ion batteries, the problem of spent graphite disposal will become increasingly prominent. It is worth noting that the EU's "New Battery Law" has officially taken effect in August 2023. The regulation stipulates that power batteries exported to Europe must be equipped with a "battery passport" containing information such as carbon footprint and supply chain, and sets a minimum recycling material usage ratio requirement for key raw materials of batteries by 2030.

[0003] However, current battery recycling companies mainly focus on extracting high-value scarce metal elements (such as Li, Co, Ni, Mn, etc.) from positive electrode materials, and lack investment in the development of regeneration and utilization technologies for spent graphite (SG). In fact, the recycling and utilization of graphite materials has long been overlooked.

[0004] Spent graphite in retired lithium batteries usually contains various impurities, including metal impurities (Fe, Cu, Al, Ca, etc.), lithium nickel cobalt manganese inorganic salts, binders, conductive agents, organic solvents and electrolyte residues, etc. If not properly treated, these spent graphites, which are classified as hazardous waste, not only cause resource waste, but also may cause serious environmental problems. Studies have shown that although graphite compounds have a relatively stable crystal structure, the interlayer van der Waals force is weakened during long-term charge and discharge cycles, and the interlayer spacing d002 can increase from the initial 0.3354 nm to 0.4 nm, and the crystal structure disorder degree increases. Scanning electron microscopy (SEM) observation shows that a large number of cracks, pores and impurity deposits appear on the surface of the cycled graphite material. It is worth noting that the differences in process formulation and working conditions of different battery manufacturers result in significant differences in the types and contents of residual impurities in spent graphite.

[0005] By developing targeted deep purification technology and graphite structure regeneration process, the directional removal of impurities and structure repair in spent graphite can be achieved, which will significantly improve the electrochemical performance of regenerated graphite. The regenerated graphite treated by optimization can be reused as a negative electrode material for lithium ion batteries, which is of great significance to promote the sustainable development of the battery industry.

[0006] In view of this, the present application is proposed. SUMMARY

[0007] The present application aims to provide a method for recycling waste graphite, a recycled graphite negative electrode material and a secondary battery.

[0008] The present application is implemented as follows:

[0009] In a first aspect, the present application provides a method for recycling waste graphite, comprising:

[0010] Roasting, oxidizing and roasting the waste graphite residue to obtain roasted graphite;

[0011] Shaping, shaping and grading the roasted graphite to obtain shaped graphite;

[0012] Graphitization, graphitizing the shaped graphite to obtain coarse graphite;

[0013] Impurity removal, removing impurities from the coarse graphite to obtain impurity-removed graphite.

[0014] Carbon coating, carbon coating the impurity-removed graphite to obtain a recycled graphite negative electrode material.

[0015] In an optional embodiment, the waste graphite residue includes graphite and oxides or sulfates of Fe, Ca, Cu, AL, Ni, Co, Mn, Li and Na;

[0016] And / or, the waste graphite residue is a solid phase residue obtained after the battery black powder is leached with sulfuric acid.

[0017] In an optional embodiment, the roasting temperature is 400-800 DEG C, the roasting time is 1-2 h, and the roasting atmosphere is an oxidizing atmosphere;

[0018] And / or, the oxidation roasting step has a gauge pressure of 5-20 pa;

[0019] And / or, the roasting step satisfies ∣ε-η∣≤5%, wherein ε=(waste graphite residue weight-roasted graphite weight) / waste graphite residue weight*100%; The mass fraction of volatile matter in the waste graphite residue.

[0020] And / or, the roasted graphite satisfies the following conditions: the mass fraction of ash is 5.0%-5.3%, the mass fraction of volatile matter is 0.1%-0.4%, the specific surface area is 11.0m 2 / g-16.5m 2D00 is 0.4um-0.6um, d50 is 14um-15um, d100 is 57um-66um, TD is 0.9g / cm 3 -0.95g / cm 3 , ε is 89.8%-95.8%, wherein, ε=(weight of waste graphite slag-weight of calcined graphite) / weight of waste graphite slag*100%;

[0021] In an optional embodiment, the shaped graphite satisfies D v 00 is 1.5um-2.5um, D v 50 is 12um-15um, D v 100<75um, tap density is 0.95g / cm 3 -1.1g / cm 3 , ash content is 2.0%-2.4%;

[0022] And / or, the shaping and grading is performed in one of a shaper, an air flow mill, and a sand mill; in the shaping step, the parameters of the shaper are as follows: front main machine rotation speed is 42Hz-45Hz, rear main machine rotation speed is 30Hz-35Hz, inner grading machine rotation speed is 15Hz-18Hz, outer grading machine rotation speed is 36Hz-40Hz, feeding speed is 16Hz-20Hz, and air blower rotation speed is 45Hz-55Hz.

[0023] In an optional embodiment, the graphitization is performed under vacuum condition and includes a holding segment and a cooling segment performed in sequence; in the holding segment, the graphitization temperature is 2000℃-2400℃, and the holding time is 0.5h-24h; the cooling rate of the cooling segment is 50℃ / min-150℃ / min, and the cooling segment is cooled to below 1000℃.

[0024] And / or, the mass fraction of ash of the crude graphite is 0.3%-0.7%, and the specific surface area is 2.8m 2 / g-3.9m 2 / g.

[0025] In an optional embodiment, the impurity removal step includes acid washing, water washing, and drying performed in sequence; the acid washing includes stirring a mixture including graphite, acid, and hydrogen peroxide; the impurity removal step satisfies at least one of the following characteristics:

[0026] a. The concentration of hydrogen ions in the mixture is 0.1mol / L-5mol / L;

[0027] b. The concentration of hydrogen peroxide in the mixture is 0.5mol / L-2mol / L;

[0028] c. The solid content in the mixture is ≤600g:1000L;

[0029] d. The pickling temperature is 60℃-90℃, the pickling time is 6h-48h, and the stirring speed is 30rpm-80rpm;

[0030] e. The acid is selected from at least one of sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid;

[0031] f. Wash with water 2-3 times until the pH of the washing solution is 5-7;

[0032] g. Drying is performed using flash evaporation;

[0033] h. The ash content of the purified graphite is less than 0.04%.

[0034] In an optional embodiment, a carbon-source-containing gas is passed into a reactor containing purified graphite to perform carbon deposition, forming a carbon coating layer. The carbon deposition includes at least one of the following characteristics:

[0035] A. The carbon deposition temperature is 500℃-600℃, the time is 1h-3h, and the flow rate of the carbon source is 0.5L / min-2L / min;

[0036] B. The carbon source is selected from at least one of methane, ethane, and propylene;

[0037] C. The carbon-source gas also includes nitrogen, and the flow rate of the nitrogen is 4 L / min to 6 L / min.

[0038] Carbon coating forms a core-shell structure in the regenerated graphite anode material, which can significantly reduce the specific surface area of ​​the anode material, improve the first efficiency and cycle life, and optimize its electrochemical performance.

[0039] Secondly, the present invention provides a recycled graphite anode material, which is obtained by the waste graphite recycling method described in the foregoing embodiments.

[0040] In an optional embodiment, the recycled graphite anode material has a DV50 of 10µm-16µm and a TD of 1g / cm³. 3 -1.1g / cm 3 BET is 0.6m 2 / g-0.9m 2 / g, Ti content <50ppm, Zr content <100ppm, ash content <0.1%;

[0041] And / or, in the XRD pattern of the recycled graphite anode material, the diffraction angle of the (0, 0, 2) crystal plane is 26.45°-26.48°, and the full width at half maximum (FWHM) of the diffraction peak of the (0, 0, 2) crystal plane is 0.27°-0.33°;

[0042] And / or, the grain size of the regenerated graphite negative electrode material is 27nm-33nm.

[0043] In a third aspect, the application provides a secondary battery comprising the regenerated graphite negative electrode material according to the foregoing embodiments.

[0044] The application has the following beneficial effects:

[0045] The method for regenerating waste graphite in the application not only realizes the transformation of waste into treasure, but also solves the problem of environmental pollution and waste of resources when waste graphite slag is treated as solid waste. The equipment used is mature industrial equipment in the market, which is mature, safe and reliable, and has low investment cost, and can meet the demand of large-scale production. Importantly, high-quality battery-grade graphite negative electrode material with high purity, high capacity, long cycle and good fast-charging performance can be obtained, and finally the recycling of resources is realized. BRIEF DESCRIPTION OF DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the application, and therefore should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can also be obtained without creative labor.

[0047] Figure 1 The flow chart of Example 1 of the application;

[0048] Figure 2 The SEM image of waste graphite slag related to Example 1 of the application;

[0049] Figure 3 The cross-sectional SEM image of waste graphite slag related to Example 1 of the application;

[0050] Figure 4 The XRD image of the regenerated graphite negative electrode material prepared in Example 1 of the application;

[0051] Figure 5 The cross-sectional SEM image of the regenerated graphite negative electrode material prepared in Example 1 of the application;

[0052] Figure 6 The charge-discharge curve of the regenerated graphite negative electrode material prepared in Example 1 of the application;

[0053] Figure 7 The cycle charge-discharge test curve of the regenerated graphite negative electrode material prepared in Example 1 and Example 10 of the application. DETAILED DESCRIPTION

[0054] In order to make the purposes, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below. If specific conditions are not specified in the embodiments, conventional conditions or manufacturer recommended conditions are adopted. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased in the market.

[0055] The current impurity removal and regeneration process of waste graphite negative electrode material mainly faces the following problems:

[0056] 1. Limitation of raw materials

[0057] The raw materials for recycling at the present stage mainly come from unqualified negative electrode sheets, negative electrode powders generated in the process of battery manufacturing, and waste graphite such as graphite molds and crucibles that have not been recycled. Such raw materials have the characteristics of low impurity content (ash content <2%) and complete graphite structure, and the processing technology is relatively simple. However, its inventory is limited and cannot effectively solve the recycling demand of graphite negative electrode material in large-scale retired lithium batteries. Therefore, it is particularly necessary to regenerate low-grade graphite raw materials with high impurity content.

[0058] 2. The main problems of impurity removal and regeneration of low-grade graphite raw materials

[0059] Flotation method: Although the reagent consumption is low and the cost is low, the product graphite grade (80-95%) is difficult to meet the requirements of battery-grade graphite negative electrode material (carbon content ≥99.9%).

[0060] Acid-base method: Through acid (hydrofluoric acid, hydrochloric acid, sulfuric acid) or lye treatment, combined with solid-liquid separation, washing and drying, the process is simple and the product grade can reach 99.5%. However, this method has a significant impact on material performance, it is difficult to remove insoluble sulfate impurities, and it produces wastewater containing fluorine and organic solvents, which has high safety and environmental risks.

[0061] Chlorination roasting method: heat the graphite under anaerobic conditions and pass in chlorine gas to convert metal impurities into chlorides and gasify and discharge. This process is relatively energy-saving, but due to insufficient gas-solid reaction, the product grade is low (about 98%), and the toxicity and environmental hazards of chlorine gas limit its application.

[0062] High temperature method: heat the waste graphite to 2700-3000℃, remove the impurities by high temperature decomposition and gasification, and regenerate the graphite structure. Its advantages are simple process, high product grade (up to 99.7%), but the equipment requirements are harsh, the energy consumption is extremely high, and the economic efficiency is poor.

[0063] 3. The problem of removing non-graphite carbon impurities in the graphite regeneration process

[0064] In the process of battery manufacturing and recycling, organic matters such as binders (e.g. SBR, PVDF), conductive carbon black, electrolyte and SEI film will be enriched in graphite. The existing recycling technology generally adopts high-temperature calcination (>800℃) under a protective atmosphere to decompose these organic matters, but the pyrolysis residues will form non-graphitic carbon. Such impurities have the characteristics of small particle size (<2μm), high specific surface area, high activity, difficult graphitization and low lithium intercalation capacity.

[0065] In addition, the pitch coating carbonization layer used in the process of commercial graphite manufacturing will be broken after multiple charge and discharge, resulting in its functional failure. With the increase of the number of graphite cycles, the content of non-graphitic carbon continues to accumulate, and it is difficult to effectively separate graphitized carbon and non-graphitic carbon by conventional physical and chemical methods (such as acid washing and high-temperature graphitization).

[0066] In summary, the existing technology still cannot balance high-efficiency impurity removal, high-quality regeneration, economic feasibility and environmental friendliness, and it is urgent to develop a more optimized recycling process.

[0067] To overcome the above problems, the embodiments of the present application provide a method for recycling waste graphite, comprising:

[0068] calcination, oxidizing and calcining the waste graphite residue to obtain calcined graphite;

[0069] shaping, shaping and grading the calcined graphite to obtain shaped graphite;

[0070] graphitization, graphitizing the shaped graphite to obtain crude graphite;

[0071] impurity removal, removing impurities from the crude graphite to obtain impurity-removed graphite;

[0072] carbon coating, carbon-coating the impurity-removed graphite to obtain a regenerated graphite negative material.

[0073] The method for recycling waste graphite of the present application not only realizes "waste into treasure", solves the problem of environmental pollution and waste of resources when waste graphite residue is treated as solid waste, but also uses market-mature industrialized equipment, which is mature, safe and reliable, and has low investment cost, and can meet the demand of large-scale production. Importantly, high-quality battery-grade graphite negative materials with high purity, high capacity, long cycle, and good fast-charging performance can be obtained, and finally the recycling of resources "waste into treasure" is realized.

[0074] In optional embodiments, the waste graphite residue includes graphite and oxides or sulfates of Fe, Ca, Cu, AL, Ni, Co, Mn, Li and Na;

[0075] And / or, the waste graphite residue is a solid residue obtained after sulfuric acid leaching of battery black powder.

[0076] The waste lithium ion battery is discharged, crushed, calcined and sieved to remove copper and aluminum, to obtain a battery black powder, the battery black powder is washed by sulfuric acid leaching and then subjected to solid-liquid separation, to obtain a leaching solution containing a large amount of valuable metal sulfate and waste graphite slag involved in the present application, and the leaching solution can be used for extracting nickel, cobalt, manganese and lithium, wherein the waste graphite slag is used as a raw material for regeneration of the waste graphite in the present application.

[0077] The waste graphite slag contains sulfate impurities, including sulfates of Fe, Ca, Cu, AL, Ni, Co, Mn, Li, Na and the like, and if the waste lithium ion battery is a waste lithium iron phosphate battery, the waste graphite slag also contains phosphate impurities.

[0078] In an optional embodiment, the calcination temperature is 400-800 DEG C, for example, 400 DEG C, 440 DEG C, 480 DEG C, 520 DEG C, 560 DEG C, 600 DEG C, 640 DEG C, 680 DEG C, 720 DEG C, 760 DEG C, 800 DEG C; the calcination time is 1-2 h, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h; the calcination atmosphere is an oxidizing atmosphere, for example, oxygen or a mixture of oxygen and compressed air, and the volume fraction of oxygen can be 20-30%;

[0079] And / or, the oxidation calcination step has a gauge pressure of 5-20 Pa, for example, 5 Pa, 6.5 Pa, 8 Pa, 9.5 Pa, 11 Pa, 12.5 Pa, 14 Pa, 15.5 Pa, 17 Pa, 18.5 Pa, 20 Pa;

[0080] And / or, the calcination step satisfies | ε-η | ≤ 5%, for example, | ε-η | is 0, 1%, 2%, 3%, 4%, 5%, wherein, ε = (the weight of the waste graphite slag - the weight of the calcined graphite) / the weight of the waste graphite slag x 100%; η = (the weight of the calcined graphite - the weight of the waste graphite slag) / the weight of the waste graphite slag x 100%; wherein, η is the mass fraction of volatile matter in the waste graphite slag. If ε-η > 5%, it indicates that the calcination temperature is too high or the calcination time is too long, resulting in overcalcination; if η-ε > 5%, it indicates that the calcination is insufficient.

[0081] And / or, the calcined graphite satisfies that the mass fraction of ash is 5.0-5.3%, for example, 5.0%, 5.03%, 5.07%, 5.1%, 5.13%, 5.17%, 5.2%, 5.23%, 5.27%, 5.3%; the mass fraction of volatile matter is 0.1-0.4%, for example, 0.1%, 0.13%, 0.17%, 0.2%, 0.23%, 0.27%, 0.3%, 0.33%, 0.37%, 0.4%; the specific surface area is 11.0-16.5 m 2 / g; the pore volume is 0.001-0.005 cm3 / g; the particle size is 0.1-0.2 mm; the tap density is 0.8-1.2 g / cm3.2 / g, for example 11.0 m2 / g, 11.6 m2 / g, 12.2 m2 / g, 12.8 m2 / g, 13.4 m2 / g, 14.0 m 2 / g, 14.6 m 2 / g, 15.2 m 2 / g, 15.8 m 2 / g, 16.5 m 2 / g; D00 is 0.4 um-0.6 um, for example 0.40 um, 0.42 um, 0.44 um, 0.46 um, 0.48 um, 0.50 um, 0.52 um, 0.54 um, 0.56 um, 0.58 um, 0.60 um; d50 is 14 um-15 um, for example 14.0 um, 14.1 um, 14.2 um, 14.3 um, 14.4 um, 14.5 um, 14.6 um, 14.7 um, 14.8 um, 14.9 um, 15.0 um; d100 is 57 um-66 um, for example 57 um, 58 um, 59 um, 60 um, 61 um, 62 um, 63 um, 64 um, 65 um, 66 um; TD is 0.9 g / cm 3 -0.95 g / cm 3 , for example 0.90 g / cm 3 , 0.91 g / cm 3 , 0.92 g / cm 3 , 0.93 g / cm 3 , 0.94 g / cm 3 , 0.95 g / cm 3 ; ε is 89.8%-95.8%, for example 89.8%, 90%, 91%, 92%, 93%, 94%, 95%, 95.8%; wherein, ε=(weight of waste graphite slag-weight of calcined graphite) / weight of waste graphite slag×100%; limiting the specific surface area, particle size distribution and other parameters of the calcined graphite can preliminarily form the particles, and provide a suitable basis for subsequent shaping. Suitable specific surface area is conducive to the migration and rearrangement of carbon atoms in the subsequent graphitization process, and the particle size distribution affects the bulk density and conductivity of the material.

[0082] During the oxidation roasting process, the residual binder, SEI film, electrolyte and other organic matter in the graphite slag are fully decomposed and oxidized, while the graphite structure is hardly affected. The tail gas after oxidation roasting contains a high concentration of CO and other organic gases, and the tail gas can be treated by using a incinerator + alkaline liquid spraying method. The main reason is that graphite has extremely high crystallinity, highly stable crystal structure, extremely strong interatomic force, and excellent thermal conductivity, so heat is not easy to accumulate, and therefore graphite is not easy to react with oxygen in the air at relatively low temperatures. The non-graphite carbon after decomposition of organic matter has very high activity and is very easy to chemically react with oxygen to generate carbon monoxide or carbon dioxide.

[0083] 400℃-800℃ conditions for oxidation roasting can greatly reduce the volatile matter in the material and remove most of the organic matter such as binder. The roasting time of 1h-2h and the slight positive pressure can ensure that the reaction proceeds sufficiently, so that the ash content of the roasted graphite is reduced to 5.0%-5.3%, the volatile matter is reduced to 0.1%-0.4%, and at the same time, the specific surface area is greatly increased to 8-20m 2 / g. This provides purer raw materials for subsequent steps and provides more active sites, which is beneficial to the rapid intercalation / deintercalation of lithium ions during charging and discharging, and improves the fast charging performance.

[0084] In optional embodiments, the shaped graphite satisfies Dv00 is 1.5um-2.5um, for example 1.5um, 1.6um, 1.7um, 1.8um, 1.9um, 2.0um, 2.1um, 2.2um, 2.3um, 2.4um, 2.5um; D v 50 is 12um-15um, for example 12.0um, 12.3um, 12.6um, 12.9um, 13.2um, 13.5um, 13.8um, 14.1um, 14.4um, 14.7um, 15.0um; D v 100 < 75um, for example 50um, 55um, 60um, 65um, 70um, 74.0um; tap density 0.95g / cm 3 -1.1g / cm 3 , for example 0.95g / cm3, 0.96g / cm3, 0.97g / cm3, 0.98g / cm3, 0.99g / cm3, 1.00g / cm 3 , 1.01g / cm 3 , 1.02g / cm 3 , 1.03g / cm 3 , 1.04g / cm 3 , 1.05g / cm 3; ash content is 2.0%-2.4%, for example, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%;

[0085] And / or, the shaping and grading are performed in one of a shaper, an air flow mill, and a sand mill; in the shaping step, the parameters of the shaper are as follows: front main machine speed 42 Hz-45 Hz, rear main machine speed 30 Hz-35 Hz, inner classifier speed 15 Hz-18 Hz, outer classifier speed 36 Hz-40 Hz, feeding speed 16 Hz-20 Hz, and air blower speed 45 Hz-55 Hz.

[0086] In the shaping step, mechanical force is used to disperse and grind the calcined graphite, and the non-graphitized carbon layer adhered to the surface of the calcined graphite is peeled off, and at the same time, the fine powder (mainly non-graphitized carbon and a small amount of graphite micro-particles) is screened out by using a grading device, so as to control the particle size and improve the tap density.

[0087] By performing shaping and grading in the shaper and other devices, the particle size of the shaped graphite meets the requirements, and the particle shape is more regular and the particle size distribution is more uniform. This helps to improve the tap density of the material to 0.95 g / cm 3 -1.1 g / cm 3 , so as to increase the content of active substances in unit volume and improve the energy density of the battery. In addition, the shaping process can further remove part of the impurities, so that the ash content is reduced to 2.0%-2.4%, the negative effects of impurities on the performance of the battery are reduced, and the stability and cycle life of the battery are improved.

[0088] In an optional embodiment, the graphitization is performed under vacuum conditions and includes a holding segment and a cooling segment performed in sequence. In the holding segment, the graphitization temperature is 2000°C-2400°C, for example, 2000°C, 2040°C, 2080°C, 2120°C, 2160°C, 2200°C, 2240°C, 2280°C, 2320°C, 2360°C, 2400°C; the holding time is 0.5h-24h, for example, 0.5h, 2.7h, 5.0h, 7.3h, 9.6h, 11.9h, 14.2h, 16.5h, 18.8h, 21.1h, 24h; preferably 3h-5h; the cooling rate of the cooling segment is 50°C / min-150°C / min, for example, 50°C / min, 55°C / min, 60°C / min, 65°C / min, 70°C / min, 75°C / min, 80°C / min, 85°C / min, 90°C / min, 95°C / min, 100°C / min, 110°C / min, 120°C / min, 130°C / min, 140°C / min, 150°C / min; the temperature in the cooling segment is cooled to below 1000°C;

[0089] and / or the mass fraction of the coarse graphite ash is 0.3%-0.7%, for example, 0.3%, 0.34%, 0.38%, 0.42%, 0.46%, 0.5%, 0.54%, 0.58%, 0.62%, 0.66%, 0.7%; the specific surface area is 2.8m 2 / g-3.9m 2 / g, for example, 2.8m 2 / g, 2.91m 2 / g, 3.02m 2 / g, 3.13m 2 / g, 3.24m 2 / g, 3.35m 2 / g, 3.46m 2 / g, 3.57m 2 / g, 3.68m 2 / g, 3.79m 2 / g, 3.9m 2 / g.

[0090] Before the graphitization step, in order to ensure that air in the graphitization equipment is as much as possible to be discharged, first vacuumize to below 200pa, then replace 1-3 times by introducing argon to normal pressure, and finally vacuumize to negative pressure for the graphitization step. Under the condition of high temperature vacuumization at 2000-2400℃, heat preservation for 0.5h-24h can make carbon atoms in the shaped graphite rearrange to form a highly ordered graphite structure, and improve the graphitization degree. The graphite structure with high crystallinity is beneficial to the embedding and extraction of lithium ions, and can improve the charge-discharge performance and cycle stability of the battery. After graphitization, the defects (nanoscale voids, cracks, dislocations, etc.) in the graphite crystal structure are significantly reduced, and the grain size of the graphite is obviously reduced; further, the specific surface area of the coarse graphite after graphitization is 2.8m 2 / g-3.9m 2 / g, which is lower than that of the shaped graphite, can reduce the contact area of the electrode and the electrolyte, reduce the irreversible capacity loss, and improve the first charge-discharge efficiency and cycle performance of the battery.

[0091] In the graphitization temperature range, chemical reactions such as decomposition, reduction, and gasification of part of the insoluble sulfate impurities in the shaped graphite can occur. Some of the impurities from the positive electrode material, such as ZrO2, TiO2, etc., have high melting points and stable chemical properties, and are not easy to react with acids and bases. In this temperature range, they can be converted into corresponding carbonates that are easily soluble in acid and removed in the subsequent impurity removal step. Through rapid cooling technology, the grain size of the graphite crystal can be reduced, and more grain boundaries can be retained, so that the graphite primary particles have significant anisotropy, which can reduce the internal stress caused by volume expansion during lithium intercalation, thereby improving the cycle life of the graphite negative electrode. At the same time, smaller grains mean shorter lithium ion migration paths, and more grain boundaries mean more lithium ion diffusion channels, which can greatly improve the fast-charging performance of the regenerated graphite negative electrode material.

[0092] In an optional embodiment, the impurity removal step includes acid washing, water washing, and drying in sequence, the acid washing includes stirring a mixture including graphite, acid, and hydrogen peroxide; and the impurity removal step satisfies at least one of the following characteristics:

[0093] a. The concentration of hydrogen ions in the mixture is 0.1 mol / L-5 mol / L, such as 0.1 mol / L, 0.6 mol / L, 1.1 mol / L, 1.6 mol / L, 2.1 mol / L, 2.6 mol / L, 3.1 mol / L, 3.6 mol / L, 4.1 mol / L, 4.6 mol / L, 5 mol / L;

[0094] b. The concentration of hydrogen peroxide in the mixture is 0.5 mol / L-2 mol / L, such as 0.5 mol / L, 0.65 mol / L, 0.8 mol / L, 0.95 mol / L, 1.1 mol / L, 1.25 mol / L, 1.4 mol / L, 1.55 mol / L, 1.7 mol / L, 1.85 mol / L, 2 mol / L;

[0095] c. The solid content in the mixture is ≤600 g:1000 L;

[0096] d. The acid washing temperature is 60°C-90°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C; the acid washing time is 6h-48h, such as 6h, 10h, 14h, 18h, 22h, 26h, 30h, 34h, 38h, 42h, 48h; and the stirring speed is 30rpm-80rpm, such as 30rpm, 35rpm, 40rpm, 45rpm, 50rpm, 55rpm, 60rpm, 65rpm, 70rpm, 75rpm, 80rpm;

[0097] e. the acid is selected from at least one of sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid;

[0098] f. the water washing is performed 2-3 times until the pH of the washing solution is 5-7;

[0099] g. the drying is performed by flash drying;

[0100] h. the ash content of the impurity-removed graphite is less than 0.04%.

[0101] By controlling the parameters such as the concentration of hydrogen ions, the concentration of hydrogen peroxide, the solid content, the acid washing temperature and time during the acid washing process, the metal impurities and other impurities in the crude graphite can be effectively removed. The water washing is performed until the pH of the washing solution is 5-7, which ensures that the impurities are fully removed, and the ash content of the impurity-removed graphite is less than 0.04%. The reduction of impurities can reduce the risk of internal short circuit of the battery and improve the safety and stability of the battery. In addition, the acid washing process can also activate the surface of the graphite and improve the chemical properties of the surface of the graphite, which is beneficial to the uniform deposition of the carbon layer in the subsequent carbon coating process and improves the coating effect.

[0102] In optional embodiments, a carbon source-containing gas is introduced into a reactor containing the impurity-removed graphite to perform carbon deposition to form a carbon coating layer, and the carbon deposition includes at least one of the following features:

[0103] A. the temperature for carbon deposition is 500-600°C, for example, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C; the time is 1-3h; the flow rate of the carbon source is 0.5-2L / min, for example, 0.5L / min, 0.65L / min, 0.8L / min, 0.95L / min, 1.1L / min, 1.25L / min, 1.4L / min, 1.55L / min, 1.7L / min, 1.85L / min, 2L / min;

[0104] B. the carbon source is selected from at least one of methane, ethane and propylene;

[0105] C. the carbon source-containing gas further includes nitrogen, and the flow rate of the nitrogen is 4-6L / min, for example, 4L / min, 4.2L / min, 4.4L / min, 4.6L / min, 4.8L / min, 5L / min, 5.2L / min, 5.4L / min, 5.6L / min, 5.8L / min, 6L / min.

[0106] The presence of a carbon coating can significantly reduce the specific surface area of ​​the negative electrode material, reduce the direct contact between the electrolyte and graphite, inhibit the excessive growth of the SEI film, and improve the first-time efficiency; it can buffer the volume change of graphite during charging and discharging, enhance the stability of the electrode structure, and thus improve the cycle life of the battery; it can also improve the conductivity of the material, which is conducive to the rapid migration of lithium ions and improve the rate performance of the battery.

[0107] The present invention also provides a recycled graphite anode material, which is obtained by the waste graphite recycling method described in the foregoing embodiments.

[0108] In an optional embodiment, the recycled graphite anode material DV50 is 10um-16um, for example 10um, 11um, 12um, 13um, 14um, 15.0um, or 16.0um; the moderate particle size can reduce the gaps between particles, increase the tap density, and at the same time shorten the lithium-ion insertion / extraction distance, accelerate the kinetic reaction, reduce polarization, and help improve the battery rate performance and cycle stability.

[0109] The TD of the recycled graphite anode material is 1 g / cm³. 3 -1.1g / cm 3 For example, 1 g / cm³, 1.01 g / cm³, 1.02 g / cm³, 1.03 g / cm³. 3 1.04 g / cm 3 1.05g / cm 3 1.06 g / cm 3 1.07g / cm 3 1.08g / cm 3 1.09 g / cm 3 1.1g / cm 3 A higher tap density (TD) means denser particle packing, which can increase the volumetric energy density of the electrode. Closer packing reduces electrolyte wetting dead zones, lowers interfacial impedance, and simultaneously enhances electrode structural stability, extending battery life.

[0110] The BET of the recycled graphite anode material is 0.6m. 2 / g-0.9m 2 / g, for example 0.60m² / g, 0.63m² / g, 0.66m² / g, 0.69m² / g. 2 / g, 0.72m 2 / g, 0.75m 2 / g, 0.78m 2 / g, 0.81m 2 / g, 0.84m 2 / g, 0.87m 2 / g, 0.90m 2Low specific surface area (BET) can reduce the contact area between graphite and electrolyte, reduce side reactions (such as excessive generation of SEI film), reduce the irreversible capacity loss of the first charge and discharge (improve the initial efficiency). At the same time, it can reduce the consumption rate of electrolyte, delay the impedance growth during the cycle process, and improve the cycle life.

[0111] The Ti content of the regenerated graphite negative electrode material is <50ppm, the Zr content is <100ppm, and the ash content is <0.1%. Controlling metal impurities (Ti, Zr) and ash can avoid impurities as catalysts to exacerbate electrolyte decomposition or cause lithium ion migration obstacles. Low impurity content can reduce battery self-discharge, reduce capacity decay during the cycle process, and improve electrode chemical stability and safety.

[0112] In an optional embodiment, in the XRD pattern of the regenerated graphite negative electrode material, the diffraction angle of the (0, 0, 2) crystal face is 26.45°-26.48°, such as 26.45°, 26.455°, 26.46°, 26.465°, 26.47°, 26.475°, 26.48°; the half-height width of the (0, 0, 2) crystal face diffraction peak is 0.27°-0.33°, such as 0.27°, 0.28°, 0.29°, 0.30°, 0.31°, 0.32°, 0.33°; the diffraction angle corresponds to a graphite interlayer spacing close to ideal graphite (about 0.335nm), indicating that the graphitization degree is high and the crystal structure is regular, which is beneficial to the rapid embedding / extraction of lithium ions. Narrow half-height width indicates that the crystal grain is complete and has few defects, which can reduce the diffusion resistance of lithium ions and improve the rate performance and cycle stability.

[0113] In an optional embodiment, the grain size of the regenerated graphite negative electrode material is 27nm-33nm, such as 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm. A grain size that is too large is prone to cracking due to stress, and a grain size that is too small has many defects and poor stability. The grain size in this range can balance the structural stability and lithium ion diffusion efficiency, and improve the cycle life and rate performance of the material.

[0114] The embodiments of the present application also provide a secondary battery comprising the regenerated graphite negative electrode material of the foregoing embodiments.

[0115] In summary, the present application has the following advantages:

[0116] 1. The present application uses acid leaching graphite slag produced during mechanical crushing of retired lithium ion batteries and wet metallurgical recovery of valuable metals such as nickel, cobalt, manganese and lithium as raw material. The raw material has the characteristics of wide source, but due to the complex and high content of impurities, it is difficult to remove impurities.

[0117] 2. For the above raw materials, firstly, through the oxidation roasting treatment: on the one hand, the organic impurities such as binders and electrolyte in it are fully pyrolyzed and carbonized to form non-graphitized carbon, and the adhesion between graphite particles is destroyed; on the other hand, by using the chemical activity difference between non-graphitized carbon and graphitized carbon, most of the non-graphitized carbon (such as pyrolysis residual carbon, conductive carbon, etc.) is oxidized and removed. Subsequently, through shaping and grading, not only the deep removal of non-graphitized carbon in waste graphite is realized, but also the particle size and morphology thereof are regulated, which is not only conducive to the recycling of graphite for multiple times, but also enables the trace metal impurities wrapped in the graphite particles to be separated, thereby laying a foundation for subsequent deep impurity removal.

[0118] 3. After the oxidation roasting and shaping and grading, a graphitization treatment at a temperature of 2000℃ or above is adopted to realize deep impurity removal and performance improvement: low-melting-point impurities are decomposed and gasified at high temperature; high-melting-point impurities (such as Ca, Zr, Ti, etc.) that are insoluble in acid form carbides, which can be effectively removed through acid reaction, so that the ash content is greatly reduced to below 0.1%. At the same time, the high-temperature environment can repair the defects in the layered structure of the waste graphite, thereby significantly improving the energy density and cycle life of the regenerated graphite negative electrode material.

[0119] 4. After the high-temperature treatment, a forced rapid cooling technology is adopted to accurately regulate the crystal structure of the material, enhance the mechanical properties thereof, and further improve the electrochemical performance.

[0120] 5. Finally, through a gas-phase carbon coating treatment, the problem of difficulty in controlling the thickness and uniformity of the carbon coating layer on the surface of the material in the traditional pitch coating carbonization process is solved, and the performance of the material is further optimized.

[0121] 6. The systematic solution provided by the present application not only realizes the transformation of waste into treasure, but also solves the problems of environmental pollution and waste of resources when the waste graphite slag is treated as solid waste. At the same time, the equipment used is a mature industrialization equipment in the market, which is mature, safe and reliable, and has low investment cost, and can meet the demand of large-scale production.

[0122] The features and performance of the present application are further described in detail in combination with the following examples.

[0123] Example 1

[0124] The present embodiment provides a method for regenerating waste graphite, and the flow is as shown in Figure 1 The present embodiment provides a method for regenerating waste graphite, and the flow is as shown in

[0125] S1: Take a random batch of waste graphite slag in Table 1, and the SEM image is as shown in Figure 2 The present embodiment provides a method for regenerating waste graphite, and the flow is as shown in Figure 3The surface of the waste graphite slag observed under a scanning electron microscope has a large number of structural defects such as voids and cracks, and a small amount of inclusions below 2 um are mainly non-graphitic carbon such as binders and conductive agents. The medium volatile matter of the waste graphite slag mainly comes from organic impurities such as binders, residual separators and electrolyte, and the low capacity and low initial efficiency are mainly caused by structural defects, high impurities and high specific surface area. Figure 2 As can be seen from the data in Table 1, the waste graphite slag has high impurity content, wide particle size distribution, porous particle surface and poor electrochemical performance, and cannot meet the standard of graphite negative electrode material.

[0126] Table 1

[0127]

[0128] The waste graphite slag is heated to 550 DEG C in an electric rotary kiln of ZY / HZR type, compressed air is introduced at the same time, the furnace pressure is controlled to be slightly positive, 5-20 pa, and the baking treatment is carried out for 1 h to obtain baked graphite. The mass fraction of ash is 5.12%, the mass fraction of volatile matter is 0.32%, the specific surface area is 12.06 m 2 / g, D00=0.54 um, d50=14.12 um, d100=57.852 um, TD=0.93 g / cm 3 , ε=95.3%.

[0129] S2: The baked graphite in step S1 is shaped by a V60 type shaper, the front main machine speed is 45 hz, the rear main machine speed is 30 hz, the inner classifier speed is 18 hz, the outer classifier speed is 38 hz, the feeding speed is 18 hz, and the air blower speed is 50 hz. The shaped graphite obtained has d00=1.87 um, d50=14.63 um, d100=51.15 um, TD=1.03 g / cm 3 , and the ash content is 2.35%.

[0130] S3: The shaped graphite is put into a thermal equipment, vacuumized to below 200 pa, then argon is introduced to replace the air twice, vacuumized again to 80 kPa , heated to 2400 DEG C and kept for 2 h, then forcedly cooled to 800 DEG C at an average cooling speed of about 100 DEG C / min, and then cooled with the furnace to obtain crude graphite. The mass fraction of ash is 0.35%, and the specific surface area is 3.26 m 2 / g.

[0131] S4: The crude graphite described in step S3 is mixed with a mixture having a solid-liquid ratio of 500 g / L, wherein the acid is sulfuric acid, the H+ concentration is 2 mol / L, and the hydrogen peroxide concentration is 0.5 mol / L. The mixture is heated to 80°C and stirred at a stirring speed of 50 rpm for 6 hours. After acid washing, the graphite is washed with water for 2-3 times until the washing liquid has a pH of 5.6. The washed graphite is dried and depolymerized using an XZG type rotary flash drying device to obtain the impurity-removed graphite, and the ash content of the impurity-removed graphite is 0.02%.

[0132] S5: The impurity-removed graphite is placed in a gas phase deposition furnace. The furnace is first vacuumed to a pressure below 50 Pa, then nitrogen gas is introduced and exhausted for 30 minutes. The nitrogen flow is then adjusted to 5 L / min, and the material is heated to 500°C. Methane gas is then introduced at a flow rate of 2 L / min, and the deposition reaction time is controlled to 1 hour. After that, the carbon source gas is turned off, and the regenerated graphite negative electrode material with a core-shell structure is obtained after cooling. The XRD pattern is as shown in Figure 4 . After sampling and plasma cutting, the cross section is observed using a scanning electron microscope, and the results are as shown in Figure 5 . Carbon deposition can significantly reduce the specific surface area, improve the initial efficiency and cycle life, and optimize the electrochemical performance.

[0133] Example 2:

[0134] The present embodiment provides a method for regenerating waste graphite, which specifically comprises the following steps:

[0135] S1: A random batch of waste graphite slag described in Table 1 is heated to 600°C using an electric rotary kiln with a model number of ZY / HZR. Compressed air is introduced at the same time, and the furnace pressure is controlled to be slightly positive, 5-20 Pa. The roasted graphite is obtained after roasting treatment for 1.5 hours. The ash content of the roasted graphite is 5.15% by mass fraction, the volatile content is 0.28% by mass fraction, the specific surface area is 11.06 m 2 / g, D00 = 0.57 um, d50 = 14.22 um, d100 = 58.84 um, TD = 0.93 g / cm 3 , and ε = 95.1%.

[0136] S2: The roasted graphite described in step S1 is shaped using a V60 shaper. The front main machine rotates at a speed of 45 Hz, the rear main machine rotates at a speed of 35 Hz, the inner classifier rotates at a speed of 15 Hz, the outer classifier rotates at a speed of 38 Hz, the feeding speed is 18 Hz, and the induced fan rotates at a speed of 50 Hz. The shaped graphite obtained has a d00 of 2.23 um, a d50 of 14.79 um, a d100 of 42.31 um, a TD of 1.07 g / cm 3 , and an ash content of 2.23%.

[0137] S3: Put the shaped graphite into a thermal equipment, first vacuumize to below 200 pa, then introduce argon to normal pressure for replacement twice, then vacuumize to 70 kpa, heat to 2300℃ and keep constant temperature for 2h, then forcedly cool to 600℃ at an average cooling speed of about 90℃ / min, then cool with the furnace to obtain crude graphite, test the mass fraction of ash content of the crude graphite according to the national standard GBT 3521-2023, which is 0.34%, and the specific surface area is 2.87m 2 / g;

[0138] S4: Prepare a mixture according to a solid-liquid ratio of 450g / L with the crude graphite in step S3, wherein the acid is hydrochloric acid, the H+ concentration is 2mol / L, and the hydrogen peroxide concentration is 0.5mol / L, heat to 80℃ and stir at a stirring speed of 50rpm for 12h. Wash the acid-washed graphite for 2-3 times until the washing liquid PH is 5.7, then dry and depolymerize the washed graphite by using an XZG type rotary flash drying equipment to obtain impurity-removed graphite, and test the ash content of the impurity-removed graphite, which is 0.03%;

[0139] S5: Put the impurity-removed graphite into a gas phase deposition furnace, first vacuumize to below 50pa, then introduce nitrogen for 30min, then adjust the nitrogen flow to 5L / min, heat the material to 520℃, then introduce ethane gas at a flow rate of 1.5L / min, control the deposition reaction time to be 1.5h, then close the carbon source gas, and cool to obtain a core-shell structure of regenerated graphite negative electrode material.

[0140] Example 3:

[0141] The embodiment provides a method for regenerating waste graphite, which specifically comprises the following steps:

[0142] S1: Randomly take a batch of waste graphite slag from Table 1, heat to 700℃ using an electric rotary kiln with a model of ZY / HZR, at the same time, introduce compressed air, control the furnace pressure to be slightly positive pressure state, 5-20pa, and keep constant temperature for 2h to obtain calcined graphite, test the mass fraction of ash content of the calcined graphite according to the national standard GBT 3521-2023, which is 5.30%, the mass fraction of volatile matter is 0.23%, the specific surface area is 14.21m 2 / g, D00=0.55um, d50=14.37um, d100=65.82um, TD=0.90g / cm 3 , ε=92.1%;

[0143] S2: The calcined graphite described in step S1 is subjected to shaping treatment using a V60 shaper, with a front main machine speed of 45 hz, a rear main machine speed of 35 hz, an inner classifier speed of 15 hz, an outer classifier speed of 38 hz, a feeding speed of 18 hz, and an air blower speed of 50 hz. The shaped graphite obtained has a d00 of 2.23 um, a d50 of 14.79 um, a d100 of 42.31 um, a TD of 1.07 g / cm3, and an ash content of 2.16%.

[0144] S3: The shaped graphite is placed into a thermal equipment, vacuumed to below 200 pa, and then argon is introduced to replace the air twice to reach normal pressure. The vacuum is then re-applied to 60 kpa, and the graphite is heated to 2200℃ and kept at this temperature for 3 h. The graphite is then cooled to 800℃ at an average cooling rate of about 80℃ / min, and then cooled with the furnace to obtain crude graphite. The ash content of the crude graphite is 0.46% by mass fraction, and the specific surface area is 3.2 m 2 / g according to the national standard GBT 3521-2023.

[0145] S4: The crude graphite described in step S3 is mixed with an acid according to a solid-liquid ratio of 500 g / L, where the acid is nitric acid with a H+ concentration of 2 mol / L, and the hydrogen peroxide concentration is 1 mol / L. The mixture is heated to 80℃ and stirred at a stirring speed of 50 rpm for 18 h. The pickled graphite is washed with water for 2-3 times until the washing liquid has a pH of 6.2. The washed graphite is then dried and depolymerized using an XZG rotary flash drying device to obtain impurity-removed graphite, which has an ash content of 0.03%.

[0146] S5: The impurity-removed graphite is placed into a gas phase deposition furnace, vacuumed to below 50 pa, and then nitrogen gas is introduced to replace the air for 30 min. The nitrogen flow is then adjusted to 5 L / min, and the material is heated to 540℃. Then, propylene gas is introduced at a flow rate of 1 L / min, and the deposition reaction time is controlled to be 2 h. After that, the carbon source gas is turned off, and the material is cooled to obtain a core-shell structure regenerated graphite negative electrode material.

[0147] Example 4:

[0148] The present embodiment provides a method for regenerating waste graphite, which specifically comprises the following steps:

[0149] S1: A random batch of waste graphite slag described in Table 1 is heated to 800℃ using an electric rotary kiln with a model number of ZY / HZR, while compressed air is introduced to control the furnace pressure to be slightly positive, 5-20 pa, and heat preservation is performed for 1 h to obtain calcined graphite. The ash content of the calcined graphite is 5.22% by mass fraction, the volatile content is 0.16% by mass fraction, and the specific surface area is 16.45 m 2g / cm, D00=0.52um, d50=14.72um, d100=61.65um, TD=0.92g / cm 3 , ε=89.8%;

[0150] S2: The calcined graphite described in step S1 is subjected to shaping treatment using a V60 type shaper, with a front main machine speed of 42hz, a rear main machine speed of 35hz, an inner classifier speed of 15hz, an outer classifier speed of 38hz, a feeding speed of 18hz, and an air blower speed of 50hz. The shaped graphite obtained has d00=2.35um, d50=15.76um, d100=44.5um, and TD=1.06g / cm. 3 , with an ash content of 2.15%.

[0151] S3: The shaped graphite is placed into a thermal equipment, vacuumed to below 200pa, and then argon is introduced to replace the air twice to reach normal pressure. The vacuum is then re-applied to 50kpa, and the graphite is heated to 2100℃ and kept at this temperature for 4h. The graphite is then cooled to 800℃ at an average cooling speed of 70℃ / min, and then cooled with the furnace to obtain crude graphite. The ash content of the crude graphite is 0.50% by mass fraction, and the specific surface area is 3.46m 2 / g, according to the national standard GBT 3521-2023.

[0152] S4: The crude graphite described in step S3 is mixed with a mixture according to a solid-liquid ratio of 500g / L, with hydrofluoric acid as the acid, a H+concentration of 1.0mol / L, and a hydrogen peroxide concentration of 0.5mol / L. The mixture is heated to 60℃ and stirred at a stirring speed of 50rpm for 24h. The acid-washed graphite is washed with water for 2-3 times until the washing liquid has a PH of 6.0. The washed graphite is then dried and depolymerized using an XZG type rotary flash drying equipment to obtain impurity-removed graphite, with an ash content of 0.02%.

[0153] S5: The impurity-removed graphite is placed into a gas phase deposition furnace, vacuumed to below 50pa, and then nitrogen is introduced to replace the air for 30min. The nitrogen flow is then adjusted to 5L / min, and the material is heated to 560℃. Methane gas is then introduced at a flow rate of 1L / min, and the deposition reaction time is controlled to be 2.5h. The carbon source gas is then turned off, and the material is cooled to obtain a core-shell structure regenerated graphite negative electrode material.

[0154] Example 5:

[0155] The embodiment provides a method for regenerating waste graphite, which specifically comprises the following steps:

[0156] S1: Randomly take a batch of waste graphite slag described in Table 1, heat it to 550℃ using an electric rotary kiln of model ZY / HZR, while passing in compressed air, control the furnace pressure to be slightly positive, 5-20 pa, and keep it for 1h to carry out roasting treatment to obtain roasted graphite, test its ash content according to the national standard GBT 3521-2023, the mass fraction of volatile matter is 0.34%, the specific surface area is 11.87m 2 / g, D00=0.48um, d50=14.83um, d100=60.96um, TD=0.92g / cm 3 , ε=95.8%;

[0157] S2: Use a V60 shaper to shape the roasted graphite described in step S1, the front main machine speed is 45hz, the rear main machine speed is 30hz, the inner classifier speed is 15hz, the outer classifier speed is 38hz, the feeding speed is 18hz, and the air blower speed is 50hz. The shaped graphite obtained has d00=2.15um, d50=15.739um, d100=48.1um, TD=1.06g / cm 3 , and the ash content is 2.10%.

[0158] S3: Put the shaped graphite into a thermal equipment, first vacuumize it to below 200pa, then pass in argon to replace it to normal pressure for 2 times, then vacuumize it to 40kpa to heat it to 2000℃ and keep it at constant temperature for 4h, then forcibly cool it to 800℃ at an average cooling speed of 60℃ / min, then cool it with the furnace to obtain crude graphite, test its ash content according to the national standard GBT 3521-2023, the specific surface area is 3.86m 2 / g;

[0159] S4: According to a solid-liquid ratio of 500g / L, configure a mixture for the crude graphite described in step S3, the acid is sulfuric acid, the H+ concentration is 2mol / L, and the hydrogen peroxide concentration is 0.5mol / L, heat it to 80℃ and stir it at a stirring speed of 50rpm to make it react for 48h. Wash the pickled graphite with water for 2-3 times until the washing liquid PH is 6.0, then use an XZG rotary flash drying equipment to dry and depolymerize the water-washed graphite to obtain impurity-removed graphite, and test its ash content, which is 0.04%.

[0160] S5: Put the impurity-removed graphite into a gas phase deposition furnace, first vacuumize it to below 50pa, then pass in nitrogen to empty it for 30min, then adjust the nitrogen flow to 5L / min, heat the material to 580℃, then pass in methane gas at a flow rate of 0.5L / min, control the deposition reaction time to be 3h, then close the carbon source gas, and cool it to obtain a core-shell structure of regenerated graphite negative electrode material.

[0161] Example 6

[0162] The present example provides a method for recycling waste graphite, which is different from example 5 in that the graphitization temperature is 1800℃.

[0163] Example 7

[0164] The present example provides a method for recycling waste graphite, which is different from example 1 in that the cooling rate in the graphitization step is about 150℃ / min, and then the crude graphite is obtained by furnace cooling.

[0165] Example 8

[0166] The present example provides a method for recycling waste graphite, which is different from example 1 in that hydrogen peroxide is not used in the acid pickling process.

[0167] Example 9

[0168] The present example provides a method for recycling waste graphite, which is different from example 1 in that the acid pickling process is carried out at 25℃ without heating.

[0169] Example 10

[0170] The present example provides a method for recycling waste graphite, which is different from example 1 in that the furnace cooling method is used to cool to below 800℃, and the average cooling rate is about 15℃ / min.

[0171] Example 11

[0172] The present example provides a method for recycling waste graphite, which is different from example 1 in that the roasting temperature is too high, which is 900℃.

[0173] Example 12

[0174] The present example provides a method for recycling waste graphite, which is different from example 1 in that the roasting temperature is too low, which is 300℃.

[0175] Comparative Example 1

[0176] The present example provides a method for recycling waste graphite, which is different from example 1 in that no shaping process is performed.

[0177] Comparative Example 2

[0178] The present example provides a method for recycling waste graphite, which is different from example 1 in that no graphitization treatment is performed.

[0179] Comparative Example 3

[0180] The embodiment provides a method for regenerating waste graphite, which is different from the method in the embodiment 1 in that no acid pickling and impurity removing treatment is performed, and the ash content is obviously high.

[0181] Test Example 1

[0182] In order to test the electrochemical performance of the regenerated graphite, the regenerated graphite material obtained in each of the above embodiments and the comparative example is sieved through a 200-mesh sieve and then assembled into a button cell for testing, the positive electrode of the cell is a lithium sheet, and the negative electrode material of the cell includes the regenerated graphite negative electrode material (91.6% by mass), acetylene black (1.8% by mass), and polyvinylidene fluoride (6.6% by mass) (PVDF), the pulp solid content is 43.5%, and the solvents used are EC (ethylene carbonate), DMC (dimethyl carbonate), and EMC (methyl ethyl carbonate) three systems; the electrolyte is a solution with a LiPF6 concentration of 1 mol / L (wherein the volume ratio of EC, DMC, and EMC is 1:1:1), and the button cell is prepared in an argon-filled glove box. The charge and discharge test of the cell is performed on a LAND battery system, and the charge and discharge voltage range is 0.005-2 V, the gram capacity and the first coulombic efficiency at 0.1 C are measured, and the specific values are shown in Table 2, wherein the charge and discharge curve of the regenerated graphite negative electrode material cell in the embodiment 1 is as shown in FIG. 1. Figure 6 .

[0183] The metal impurity content in the regenerated graphite negative electrode material samples obtained in each of the above embodiments and the comparative example is tested by using an inductively coupled plasma instrument (ICP), and the results are shown in Table 2.

[0184] DV50 and TD are determined according to the relevant provisions in GB / T 24533.

[0185] BET is determined according to the provisions in GB / T 19587.

[0186] Ash content, refer to the determination of 7 ash content in the national standard GBT 3521-2023.

[0187] The first coulombic efficiency is calculated as the ratio of the first charge capacity to the discharge capacity.

[0188] Table 2

[0189]

[0190] Test Example 2

[0191] The regenerated graphite negative electrode material samples obtained in the above examples and comparative examples were scanned by an X-ray diffractometer at a scanning speed of 0.02° / min in the range of 2-90°, and the diffraction intensity integral curves were obtained after processing by a special software MDIjade6. The grain size of the regenerated graphite negative electrode material was calculated according to the curve, and the results are shown in Table 3. Specifically, the sample was subjected to XRD analysis, and the grain size was calculated by the Scherrer formula:

[0192] D = K * λ / (B * COS2θ)

[0193] D is the grain size, with nm as the unit;

[0194] B is the half-height width of the (0, 0, 2) crystal face diffraction peak, with radian as the unit;

[0195] 2θ is the (0, 0, 2) crystal face diffraction angle;

[0196] λ is the copper target X-ray wavelength, taking 0.154056 nm;

[0197] K is a constant, taking 0.89.

[0198] The diffraction intensity integral curve of the regenerated graphite negative electrode material obtained in the example is as shown in Figure 4 According to Figure 4 It can be seen that the purity of the regenerated graphite negative electrode material prepared in Example 1 is extremely high, and no impurity phase and impurity peak is found. The (0, 0, 2) layer spacing data is directly brought into the Franklin graphitization degree calculation formula, and the graphitization degree is as high as 93.6%, which further indicates that the structure of the regenerated graphite is fully repaired and the impurities are removed.

[0199] Table 3

[0200] Sample 2 theta / ° Half-height width / ° Crystallite size (D) / nm Shaped graphite 26.41 0.2720 32.25 Example 1 26.45 0.3201 27.41 Example 2 26.48 0.3119 28.14 Example 3 26.45 0.3154 27.82 Example 4 26.45 0.3142 27.93 Example 5 26.46 0.3131 28.03 Example 6 26.45 0.2899 30.27 Example 7 26.45 0.3260 26.92 Example 10 26.45 0.2705 32.44 Example 11 26.47 0.3118 28.15 Example 12 26.40 0.3266 26.85

[0201] From Tables 2-3, it can be seen from the comparison between Example 1 and Example 6 that the ash content and impurity content of the regenerated graphite are relatively high due to the too low graphitization temperature. Further XRD detection analysis found that the main reason is that the graphitization temperature is too low, and the high melting and boiling point insoluble impurities such as titanium and zirconium do not undergo structural transformation, mainly existing in the form of oxides, which cannot be removed by acid dissolution.

[0202] It is found by comparing Example 1 with Comparative Example 1 that if no shaping is performed, the tap density of the regenerated graphite is low, and even if the graphitization + acid washing treatment is performed, the ash content and impurity content are still relatively high, and the sample specific capacity and initial efficiency are low.

[0203] It is found by comparing Example 1 with Comparative Example 2 that if no graphitization treatment is performed, the ash content and impurity content are high, and the regenerated graphite has low specific capacity and initial efficiency.

[0204] It is found from the comparison of Example 1 and Comparative Example 3 that the ash content of the regenerated graphite is obviously high if the impurities are not removed by acid pickling.

[0205] It is found from the comparison of Example 1 and Example 8 that the ash content of the regenerated graphite is as high as 0.21% if hydrogen peroxide is not used in the acid pickling process, and the content of insoluble impurities such as Zr and Ti in the sample is obviously high as found by ICP analysis.

[0206] It is found from the comparison of Example 1 and Example 9 that the reaction is incomplete if no heating is performed in the acid pickling process, resulting in high ash content.

[0207] It is found from the comparison of Example 1 and Examples 11 and 12 that the non-graphitized carbon cannot be completely removed if the calcination temperature is too low, resulting in poor performance of the regenerated graphite, and the main reason for the small grain size is the presence of non-graphitized carbon; however, the performance will also be poor if the calcination temperature is too high.

[0208] It can be seen from the comparison of the grain size data of the comparative example and Examples 10, especially Examples 1, 7 and Example 10, that the grain size of the material can be reduced by about 12% and the mechanical properties of the material can be improved by forced rapid cooling. Under the condition of 1C charge-discharge rate, the capacity retention rate of Example 1 is as high as 90.7% and the capacity retention rate of Example 10 is only 87.5% as found by comparing the capacity retention rates of the samples of Example 1 and Example 10 after 1000 cycles of soft package test with high-nickel ternary as the positive electrode material and the samples of Example 1 and Example 10 as the negative electrode material at 45°C. Figure 7 Experiments show that the rate performance and cycle life of the material can be improved by controlling the grain size of the material.

[0209] It can be seen from the comparison of Figure 3 and Figure 5 that the internal structural defects of the treated regenerated graphite are obviously repaired, and the Figure 4 It can be seen from the XRD image of the regenerated graphite that there are significant graphite diffraction peaks and no impurity peaks are observed.

[0210] The above only describes the preferred embodiments of the present application and is not used to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for recycling of waste graphite, characterized in that, The method comprises the following steps: roasting, oxidizing roasting of waste graphite slag to obtain roasted graphite; shaping, shaping and grading of the roasted graphite to obtain shaped graphite; graphitization, graphitization of the shaped graphite to obtain crude graphite; impurity removal, impurity removal of the crude graphite to obtain impurity-removed graphite; carbon coating, carbon coating of the impurity-removed graphite to obtain regenerated graphite negative electrode material.

2. The method of claim 1, wherein the waste graphite is a waste graphite generated from a lithium ion battery. The waste graphite slag comprises graphite and oxides or sulfates of Fe, Ca, Cu, AL, Ni, Co, Mn, Li and Na; And / or, the waste graphite slag is a solid phase residue obtained after battery black powder is leached with sulfuric acid.

3. The method of claim 1, wherein the waste graphite is regenerated by the steps of: The roasting temperature is 400-800℃, the roasting time is 1-2h, and the roasting atmosphere is an oxidizing atmosphere; ​ And / or, the oxidation roasting step has a gauge pressure of 5-20pa; And / or, the roasting step satisfies |ε-η|≤5%, wherein ε=(waste graphite slag weight-roasted graphite weight) / waste graphite slag weight×100%; η=(1-φ)×100%, φ is the mass fraction of volatile matter in the waste graphite slag; and / or, the calcined graphite satisfies that the mass fraction of ash is 5.0%-5.3%, the mass fraction of volatile is 0.1%-0.4%, the specific surface area is 11.0m 2 / g-16.5m 2 / g, D00 is 0.4um-0.6um, d50 is 14um-15um, d100 is 57um-66um, TD is 0.9g / cm 3 -0.95g / cm 3 , and ε is 89.8%-95.8%, wherein, ε=(the weight of waste graphite residue-the weight of calcined graphite) / the weight of waste graphite residue*100%.

4. The method of claim 1, wherein the waste graphite is a waste graphite generated from a lithium ion battery. The shaped graphite satisfies D v 00 is 1.5 um - 2.5 um, D v 50 is 12 um - 15 um, D v 100 < 75 um, tap density 0.95 g / cm 3 - 1.1 g / cm 3 with an ash content of 2.0% - 2.4%; And / or, the shaping and grading is carried out in one of a shaper, an airflow mill and a sand mill; in the shaping step, the parameters of the shaper are front main machine speed 42-45Hz, rear main machine speed 30-35Hz, inner classifier speed 15-18Hz, outer classifier speed 36-40Hz, feeding speed 16-20Hz, and induced draft fan speed 45-55Hz.

5. The method of claim 1, wherein the waste graphite is a waste graphite generated from a lithium ion battery. The graphitization is carried out under vacuum conditions and comprises a holding segment and a cooling segment, the holding segment has a graphitization temperature of 2000-2400℃ and a holding time of 0.5-24h, and the cooling segment has a cooling rate of 50-150℃ / min and is cooled to below 1000℃; And / or, the mass fraction of the coarse graphite ash is 0.3%-0.7%, the specific surface area is 2.8m 2 / g-3.9m 2 / g.

6. The method of claim 1, wherein the waste graphite is a waste graphite generated from a lithium ion battery. The impurity removal step comprises acid washing, water washing and drying, the acid washing comprises stirring a mixture comprising graphite, acid and hydrogen peroxide; and the impurity removal step satisfies at least one of the following characteristics: a. The hydrogen ion concentration in the mixture is 0.1-5mol / L; b. The hydrogen peroxide concentration in the mixture is 0.5-2mol / L; c. The solid content in the mixture is ≤600g:1000L; d. The acid washing temperature is 60-90℃, the acid washing time is 6-48h, and the stirring speed is 30-80rpm; e. The acid is selected from at least one of sulfuric acid, nitric acid, hydrochloric acid and hydrofluoric acid; f. The water washing is performed 2-3 times, and the water washing is performed until the washing liquid has a pH of 5-7; g. The drying is performed by flash evaporation; h. The ash content of the impurity-removed graphite is less than 0.04%.

7. The method of claim 1, wherein the waste graphite is a waste graphite generated from a lithium ion battery. A carbon source-containing gas is introduced into a reactor containing the impurity-removed graphite to form a carbon coating layer, and the carbon deposition comprises at least one of the following characteristics: A. The carbon deposition temperature is 500-600℃, the time is 1-3h, and the flow rate of the carbon source is 0.5-2L / min; B. The carbon source is selected from at least one of methane, ethane and propylene; C. The carbon-containing source gas further comprises nitrogen gas, and the flow rate of the nitrogen gas is 4 L / min-6 L / min.

8. A regenerated graphite negative electrode material, characterized by, The method for regenerating waste graphite according to claim 2. 9.The regenerated graphite negative electrode material of claim 8, characterized in that, The recycled graphite anode material has a DV50 of 10µm-16µm and a TD of 1g / cm³. 3 -1.1g / cm 3 BET is 0.6m 2 / g-0.9m 2 / g, Ti content <50ppm, Zr content <100ppm, ash content <0.1%; And / or, in the XRD pattern of the regenerated graphite negative electrode material, the diffraction angle of the (0, 0, 2) crystal face is 26.45°-26.48°, and the half-height width of the (0, 0, 2) crystal face diffraction peak is 0.27°-0.33°. And / or, the grain size of the regenerated graphite negative electrode material is 27 nm-33 nm.

10. A secondary battery characterized by comprising: The regenerated graphite negative electrode material according to claim 8 or 9.

Citation Information

Patent Citations

  • Regeneration method of waste graphite of retired lithium battery, regenerated graphite and application of regenerated graphite

    CN118529726A

  • Recycling method of graphite in waste negative electrode, graphite negative electrode material, secondary battery and electric equipment

    CN119898768A

Cited By

  • Waste graphite repair material, preparation method and application thereof, and lithium secondary battery

    CN121626985A

  • Waste graphite repair material, preparation method and application thereof, and lithium secondary battery

    CN121626985B